Web-based project material inventory information system at PT XYZ using the waterfall method - Cut Zahra Malahayatinur; Antika Zahrotul Kamalia; Candra Naya (Jurnal Mandiri IT, 2026)
PT XYZ is an enterprise operating in the building contractor sector with a high intensity of material movement. Currently, the warehouse inventory management procedure in the company still relies on conventional methods using a manual physical Logbook. This mechanism triggers various operational obstacles, such as a high risk of handwriting errors (human error), stock discrepancies between physical availability and written balances, and a slow cascade of report recapitulation for management. This study aims to design and develop a Web-Based Project Material Inventory System to digitalize the entire workflow of stock management. The system development method implemented is the Waterfall model, which encompasses requirement analysis, design, implementation, testing, deployment, and maintenance. This computerized application is built using the PHP programming language with the Laravel framework, a MySQL database, and supported by a Tailwind CSS-based interface. System functionality testing was conducted through the Black Box Testing method to ensure all operational modules run according to the system requirements. The final result of this research is a centralized information system capable of managing master data (items, vendors, units, projects), processing incoming and outgoing item transactions with automatic stock calculation, and presenting inventory mutation reports in real-time. The implementation of this system has been proven to reduce warehouse administrative burdens, eliminate the risk of physical damage to paper documentation, and accelerate managerial decision-making processes at PT XYZ.